Selective inhibition of N-linked glycosylation impairs receptor tyrosine kinase processing - Elsenoor Klaver; Peng Zhao; Melanie May; Heather Flanagan-Steet; Hudson H. Freeze; Reid Gilmore; Lance Wells; Joseph Contessa; Richard Steet (The Company of Biologists, 2019)
Global inhibition of N-linked glycosylation broadly reduces glycan occupancy on glycoproteins, but identifying how this inhibition functionally impacts specific glycoproteins is challenging. This limits our understanding of pathogenesis in the congenital disorders of glycosylation (CDG). We used selective exo-enzymatic labeling of cells deficient in the two catalytic subunits of oligosaccharyltransferase - STT3A and STT3B - to monitor the presence and glycosylation status of cell surface glycoproteins. We show reduced abundance of two canonical tyrosine receptor kinases - the insulin receptor and insulin-like growth factor 1 receptor (IGF-1R) - at the cell surface in STT3A-null cells, due to decreased N-linked glycan site occupancy and proteolytic processing in combination with increased endoplasmic reticulum localization. Providing cDNA for Golgi-resident proprotein convertase subtilisin/kexin type 5a (PCSK5a) and furin cDNA to wild-type and mutant cells produced under-glycosylated forms of PCSK5a, but not furin, in cells lacking STT3A. Reduced glycosylation of PCSK5a in STT3A-null cells or cells treated with the oligosaccharyltransferase inhibitor NGI-1 corresponded with failure to rescue receptor processing, implying that alterations in the glycosylation of this convertase have functional consequences. Collectively, our findings show that STT3A-dependent inhibition of N-linked glycosylation on receptor tyrosine kinases and their convertases combines to impair receptor processing and surface localization. These results provide new insight into CDG pathogenesis and highlight how the surface abundance of some glycoproteins can be dually impacted by abnormal glycosylation.